Use of Disease-Modifying Therapies in Pediatric Relapsing-Remitting Multiple Sclerosis in the United Kingdom. Issue 4 (July 2021) - Abdel-mannan, Omar A.; Manchoon, Celeste; Rossor, Thomas; Southin, Justine-Clair; Tur, Carmen; Brownlee, Wallace; Byrne, Susan; Chitre, Manali; Coles, Alasdair; Forsyth, Rob; Kneen, Rachel; Mankad, Kshitij; et al.
Abstract : Objectives: To compare the real-world effectiveness of newer disease-modifying therapies (DMTs) vs injectables in children with relapsing-remitting multiple sclerosis (RRMS). Methods: In this retrospective, multicenter study, from the UK Childhood Inflammatory Demyelination Network, we identified children with RRMS receiving DMTs from January 2012 to December 2018. Clinical and paraclinical data were retrieved from the medical records. Annualized relapse rates (ARRs) before and on treatment, time to relapse, time to new MRI lesions, and change in Expanded Disability Status Scale (EDSS) score were calculated. Results: Of 103 children treated with DMTs, followed up for 3.8 years, relapses on treatment were recorded in 53/89 (59.5%) on injectables vs 8/54 (15%) on newer DMTs. The ARR was reduced from 1.9 to 1.1 on injectables ( p < 0.001) vs 1.6 to 0.3 on newer DMTs ( p = 0.002). New MRI lesions occurred in 77/89 (86.5%) of patients on injectables vs 26/54 (47%) on newer DMTs ( p = 0.0001). Children on newer DMTs showed longer time to relapse, time to switch treatment, and time to new radiologic activity than patients on injectables (log-rank p < 0.01). After adjustment for potential confounders, multivariable analysis showed that injectables were associated with 12-fold increased risk of clinical relapse (adjusted hazard ratio [HR] = 12.12, 95% CI = 1.64–89.87, p = 0.015) and a 2-fold increased risk of new radiologic activity (adjusted HR = 2.78, 95% CI = 1.08–7.13, p = 0.034) compared with newer DMTs. At 2 years from treatment initiation, 38/103 (37%) patients had MRI activity in the absence of clinical relapses. The EDSS score did not change during the follow-up, and only 2 patients had cognitive impairment. Conclusion: Newer DMTs were associated with a lower risk of clinical and radiologic relapses in patients compared with injectables. Our study adds weight to the argument for an imminent shift in practice toward the use of newer, more efficacious DMTs in the first instance. Classification of Evidence: This study provides Class IV evidence that newer DMTs (oral or infusions) are superior to injectables (interferon beta/glatiramer acetate) in reducing both clinical relapses and radiologic activity in children with RRMS.